Post COVID-19 multisystem inflammatory syndrome in adults: a new clinical challenge - Babu, T. Suresh; Sinha, Sudhir Chandra; Darimireddy, Siva Kumar; Chakravarthy, K. Kalyan; Sagar, Kotipalli Vidya (International Journal of Research in Medical Sciences, 2021)
The spectrum of novel coronavirus disease (COVID-19) continues to evolve since its outbreak in November 2019. Although COVID-19 most commonly causes substantial respiratory pathology, it can also result in several extra pulmonary manifestations. Association between COVID-19 disease and a multisystem inflammatory syndrome in children (MIS-C) and adolescents has now been well defined. However, case reports describing a similar phenomenon in adults are sparse. We presented a case of 42 year old male who presented 3 weeks after initial COVID-19 infection with acute ST elevation myocardial infarction, splenic artery thrombosis, generalized anasarca, with hepatic and renal dysfunction, but minimal respiratory symptoms. He had a turbulent hospital course. However timely suspicion of presence of multisystem inflammatory syndrome in adult (MIS-A) and use of hemoadsorption filters helped to save his life.